2003
DOI: 10.1086/345880
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance among Enterobacteriaceae Is Strongly Associated with the Presence of Integrons and Is Independent of Species or Isolate Origin

Abstract: This study investigated the extent to which multidrug resistance (MDR) among Enterobacteriaceae is related to DNA elements called "integrons," whether the relationship is species dependent or origin dependent, and which resistance patterns are associated with integrons. Analysis of 867 nonrepeat isolates comprising 8 species and originating from the community and 23 European hospitals showed a significant relation between MDR and integrons, independent of species or origin. Although resistance to each tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
168
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(184 citation statements)
references
References 27 publications
13
168
0
3
Order By: Relevance
“…Another research study analyzed 867 non-repeat isolates comprising 8 species, originating from the community and 23 European hospitals, and showed a significant relation between MDR and the presence of integrase genes, independent of species or origin. 13 Our study was in concordance with this research study which found 75.6% of their isolates as ciprofloxacin resistant and integron positive. We found 74.6% K.pneumoniae and 81.9% E.coli to be simultaneously resistant to other antibiotics appearing as multi drug resistant isolates, which suggest for limitations and precise use of antibiotics in our region.…”
Section: Quinolone Esbl Resistance and Integronssupporting
confidence: 93%
See 1 more Smart Citation
“…Another research study analyzed 867 non-repeat isolates comprising 8 species, originating from the community and 23 European hospitals, and showed a significant relation between MDR and the presence of integrase genes, independent of species or origin. 13 Our study was in concordance with this research study which found 75.6% of their isolates as ciprofloxacin resistant and integron positive. We found 74.6% K.pneumoniae and 81.9% E.coli to be simultaneously resistant to other antibiotics appearing as multi drug resistant isolates, which suggest for limitations and precise use of antibiotics in our region.…”
Section: Quinolone Esbl Resistance and Integronssupporting
confidence: 93%
“…One type of dynamic force which is perceived as a major crisis is located on the bacterial chromosome or a plasmid, and named as an integron helps bacteria to acquire novel combinations of resistance genes 10,11 and disseminate them along with the emergence of MDR strains. 10,[12][13][14] Five integron classes related to antibiotic resistance have been described based on the homology of their integrase genes and Class 1 integrons are the most commonly found in nosocomial and community environments, followed by class 2 ones. 15 The prevalence of integrons is high among gram-negative isolates from patients in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The role of class 1 integrons in conferring antibiotic resistance to clinical isolates of many bacterial strains is well documented (Briggs and Fratamico, 1999;Leverstein-van Hall et al, 2003;Segal et al, 2003;White et al, 2000). Fluit and Schmitz (2004) resistance (Bass et al, 1999;Sorum et al, 2003).…”
Section: Mechanisms Of Horizontal Gene Transfermentioning
confidence: 99%
“…The rapid emergence of antibiotic resistance among clinical isolates of bacteria is due to dissemination of antibiotic resistance genes by horizontal transfer (Leverstein-van Hall et al, 2003). Carbapenems, including imipenem and meropenem, are the most potent antimicrobial agents for the treatment of P. aeruginosa infections (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%